Answer:
-2y + 3 = 0
Step-by-step explanation:
x - 6y - 9 = 0
-6y - 9 = -x subtract x from both sides
6y + 9 = x divide both sides by -1
x = 8y + 6
6y + 9 = 8y + 6 replace x with 6y + 9
-2y + 9 = 6 subtract 8y from both sides
-2y + 3 = 0 subtract 6 from both sides
Answer:
c.
Step-by-step explanation:
Given:
μ = 68 in, population mean
σ = 3 in, population standard deviation
Calculate z-scores for the following random variable and determine their probabilities from standard tables.
x = 72 in:
z = (x-μ)/σ = (72-68)/3 = 1.333
P(x) = 0.9088
x = 64 in:
z = (64 -38)/3 = -1.333
P(x) = 0.0912
x = 65 in
z = (65 - 68)/3 = -1
P(x) = 0.1587
x = 71:
z = (71-68)/3 = 1
P(x) = 0.8413
Part (a)
For x > 72 in, obtain
300 - 300*0.9088 = 27.36
Answer: 27
Part (b)
For x ≤ 64 in, obtain
300*0.0912 = 27.36
Answer: 27
Part (c)
For 65 ≤ x ≤ 71, obtain
300*(0.8413 - 0.1587) = 204.78
Answer: 204
Part (d)
For x = 68 in, obtain
z = 0
P(x) = 0.5
The number of students is
300*0.5 = 150
Answer: 150
Answer:
320 cups of soup
Step-by-step explanation:
2/5= x/800
2/5 =.04
800*.04 =320 x=320
2/5 = 320/800
2/5 =0.4 is equivalent to 320/800=0.4
Answer:
Solutions:
, ![x = \frac{-3}{4} - i \sqrt{39}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-3%7D%7B4%7D%20-%20i%20%5Csqrt%7B39%7D)
Step-by-step explanation:
Given the quadratic equation, 2x² + 3x + 6 = 0, where a =2, b = 3, and c = 6:
Use the <u>quadratic equation</u> and substitute the values for a, b, and c to solve for the solutions:
![x = \frac{-b +/- \sqrt{b^{2} - 4ac} }{2a}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-b%20%2B%2F-%20%5Csqrt%7Bb%5E%7B2%7D%20-%204ac%7D%20%7D%7B2a%7D)
![x = \frac{-3 +/- \sqrt{3^{2} - 4(2)(6)} }{2(2)}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-3%20%2B%2F-%20%5Csqrt%7B3%5E%7B2%7D%20-%204%282%29%286%29%7D%20%7D%7B2%282%29%7D)
![x = \frac{-3 +/- \sqrt{9- 48} }{4}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-3%20%2B%2F-%20%5Csqrt%7B9-%2048%7D%20%7D%7B4%7D)
, ![x = \frac{-3 - i \sqrt{39} }{4}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B-3%20-%20i%20%5Csqrt%7B39%7D%20%7D%7B4%7D)
Therefore, the solutions to the given quadratic equation are:
, ![x = -\frac{3}{4} - i \sqrt{39}](https://tex.z-dn.net/?f=x%20%3D%20-%5Cfrac%7B3%7D%7B4%7D%20-%20i%20%5Csqrt%7B39%7D)